Occurrence and estimation of aflatoxins exposure in rice in Selangor, Malaysia / Anis Nabilah Norahmad Zaki - Norahmad Zaki, Anis Nabilah (2014)
Introduction: Aflatoxins are a group of naturally occurring mycotoxins which produced by Aspergillus flavus and Aspergil/us parasiticus and can be found in a large variety of food and animal feed. Rice is the most important staple food crop in Malaysia and the main source of carbohydrate. Objective: The aim of this study was to investigate the occurrence and concentration of aflatoxins (8₁, 8₂, G₁ and G₂) in rice and to evaluate the daily intake of this toxicant from rice consumption. Methodology: Rice samples were collected from four different cities of Selangor province including Klang, Kuala Selangor, Petaling and Gombak. The occurrence of afaltoxins was investigated in 96 rice samples. Analyses were done using LC-ESI MS/MS. Result: The total positive sample of aflatoxins 8₁, 8₂, G₁ and G₂ was 42.71 % in concentrations ranged from 1.330 to 4.452 ng/g. The average daily intake estimated for total aflatoxins was 28 ng/kg body weight. Conclusion: The results showed that 42.71 % of total analysed rice samples were contaminated with aflatoxins. Considering the tropical weather in Malaysia, rice stored under this condition is very susceptible to aflatoxins contamination.